2012
DOI: 10.1002/ppul.22582
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of respiratory status after esophageal atresia repair

Abstract: Impaired lung function was noted in children with repaired EA. Indeed, cardiopulmonary function tests results correlated with standard spirometric parameters and revealed minimal clinical symptoms. Moreover, many children with EA had a limited ventilatory reserve (VR). These results indicate that respiratory symptoms are often neglected in children with repaired EA and reinforce the need to provide adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 23 publications
5
36
1
1
Order By: Relevance
“…Somppi and coworkers described normal physical growth in the majority of patients aged from 3.5 to 30 years (mean 12.6 years); height was below −2 SD in 5% of patients . Mild growth retardation has been reported in school‐age children with EA . In 15 of 22 adolescents aged 14–18 years we found normal physical growth (68%) (unpublished data).…”
Section: Physical Growthmentioning
confidence: 57%
See 1 more Smart Citation
“…Somppi and coworkers described normal physical growth in the majority of patients aged from 3.5 to 30 years (mean 12.6 years); height was below −2 SD in 5% of patients . Mild growth retardation has been reported in school‐age children with EA . In 15 of 22 adolescents aged 14–18 years we found normal physical growth (68%) (unpublished data).…”
Section: Physical Growthmentioning
confidence: 57%
“…Sistonen and coworkers reported a prevalence of atopy in adults following EA repair that was comparable with that of the Finnish general population . From previous studies in younger children it is known that EA patients are at risk for decreased exercise tolerance . However, data on exercise tolerance in adolescent and adult EA survivors have – to our knowledge – never been published.…”
Section: Respiratory Morbiditymentioning
confidence: 90%
“…Two groups studied maximal exercise capacity using bicycle ergometry: Montgomery and coworkers found slightly decreased exercise capacity in EA‐patients at a mean age of 14 years, whereas Beucher and coworkers found normal VO 2 ‐max at 8 years of age . However, data from Beucher were obtained from retrospective chart analysis and 7/31 patients had to be excluded due to submaximal performance.…”
Section: Discussionmentioning
confidence: 99%
“…[123] A separate study showed how respiratory symptoms are often overlooked in children with repaired EA. [124] When evaluating lung function in 31 children, 45% of them had poor ventilatory response, and of these children, 77% were not on any pulmonary directed treatment.…”
Section: Extraintestinal Manifestationsmentioning
confidence: 99%